Scanning transmission electron microscopy analysis of Ge(O)/(graphitic carbon nitride) nanocomposite powder - Masahiro Kawasaki (2018)
© 2015 Elsevier Inc. All rights reserved. Analytical electron microscopy has revealed the structure of particles that were synthesized by chemical reaction of GeO2with NaBH4in the basic solution including graphitic carbon nitride (g-C3N4) powders. The g-C3N4was arranged by recrystallization of melamine at 600 °C under N2gas atmosphere. The samples were dried at 60 °C or 180 °C for 4 h. The g-C3N4was observed as lamellae of several ten nm or less in size and had an amorphous-like structure with a distorted lattice in an area as small as a few hundred pm in size. The reaction product was Ge(O) particles as fine as several nm in size and composed of Ge and O atoms. Most of the particles must be of GeO2 - xwith the amorphous-like structure that has also a distorted lattice in an area of a few hundred pm in size. In the sample dried at 60 °C, the particles were found to be dispersed in a wide area on the g-C3N4lamella. It is hard to recognize those particles in TEM images. The particles in the sample dried at 180 °C became larger and were easily observed as isolated lumps. Hence, these powders can be regarded as GeO2/g-C3N4or Ge/GeO2/g-C3N4nanocomposites, and expected to be applicable to anode materials for high energy Li-ion batteries due to Ge catalysis effect, accordingly.